Expressions duratives postverbales en chinois mandarin à l’interface syntactico-sémantique - Xiaoqian Zhang; Yiqin Qiu; Xiaoshi Hu (Canadian Journal of Linguistics)
<embed height="0" id="xunlei_com_thunder_helper_plugin_d462f475-c18e-46be-bd10-327458d045bd" type="application/thunder_download_plugin" width="0" />